2008
DOI: 10.1103/physreva.77.042312
|View full text |Cite
|
Sign up to set email alerts
|

Mixing times in quantum walks on the hypercube

Abstract: The mixing time of a discrete-time quantum walk on the hypercube is considered. The mean probability distribution of a Markov chain on a hypercube is known to mix to a uniform distribution in time O(n log n). We show that the mean probability distribution of a discrete-time quantum walk on a hypercube mixes to a (generally non-uniform) distribution π(x) in time O(n) and the stationary distribution is determined by the initial state of the walk. An explicit expression for π(x) is derived for the particular case… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 19 publications
1
56
0
Order By: Relevance
“…It can be shown that for an unbiased Hadamard walk on the line, the walk is almost uniformly distributed over the interval h t= p 2; t= p 2 i after t time steps (Nayak and Vishwan 2000). Extending this study, Marquezino and Portugal (2008) showed that the asymptotic distribution of a discrete-time quantum walk on the hypercube is in general not uniform, and characterized the average mixing time to this distribution. Moore and Russell (2002) analyzed both continuousand discrete-time quantum walks on the hypercube and showed that in both cases, the walk has an instantaneous mixing time at n =4.…”
Section: Walking Characteristicsmentioning
confidence: 88%
See 1 more Smart Citation
“…It can be shown that for an unbiased Hadamard walk on the line, the walk is almost uniformly distributed over the interval h t= p 2; t= p 2 i after t time steps (Nayak and Vishwan 2000). Extending this study, Marquezino and Portugal (2008) showed that the asymptotic distribution of a discrete-time quantum walk on the hypercube is in general not uniform, and characterized the average mixing time to this distribution. Moore and Russell (2002) analyzed both continuousand discrete-time quantum walks on the hypercube and showed that in both cases, the walk has an instantaneous mixing time at n =4.…”
Section: Walking Characteristicsmentioning
confidence: 88%
“…More specifically, they observed a highly uniform distribution on the line, a very fast mixing time on the cycle, and more reliable hitting times across the hypercube. Likewise Marquezino and Portugal (2008) established that for a walk on a hypercube a controlled amount of decoherence, due to randomly breaking links between connected sites, helps in obtaining and preserving a uniform distribution in the shortest possible time. Maloyer and Kendon (2007) showed that the mixing time of a discrete-time quantum walk on an N -cycle may be reduced by allowing for some decoherence from repeated measurements, provided that those measurements affect the position of the walk.…”
Section: Decoherencementioning
confidence: 99%
“…We note that it decays approximately as 1=T not only for the Sierpinski gasket but also for twodimensional lattices 11 and hypercubes. 12 This numerical result can be explained analytically. Expanding the quantum walk state in the eigenbasis that diagonalizes the evolution operator, one can obtain an explicit expression for jj" pðT ; x; yÞ À ðx; yÞjj for any initial condition.…”
Section: Limiting Distributionmentioning
confidence: 74%
“…[6][7][8][9] Quantum walks have been analyzed on two-dimensional square lattices, 10,11 and on the hypercube. 12 A spatial search using the discrete-time quantum walk model has been undertaken on the Sierpinski gasket, 13 and on the Hanoi network of degree 3. 14 A quantum walk on the dual Sierpinski gasket using the continuous-time quantum walk model has been analyzed by Agliari et al 15 In this paper, we focus our attention on discrete-time quantum walks on the Sierpinski gasket.…”
Section: Introductionmentioning
confidence: 99%
“…Many aspects of QW have been studied theoretically, for example some researches focus on the network over which the walks takes place. In this area, the QW on a line has been well studied [11][12][13][14][15][16], but other topologies such as cycles [17,18], two-dimensional lattices [19][20][21][22], or n-dimensional hypercubes [23,24] have also been investigated.…”
Section: Introductionmentioning
confidence: 99%